Assessing the role of NGOs in alleviating poverty among aborigines habitat in India and Malaysia - Naila Aaijaz; Mohamed Dahlan Ibrahim; Noraani Mustapha; Yah Awg Nik (2011)
The greatest challenge to assuage poverty is revealed through the existing poverty situation amongst the aborigines in Malaysia and India where most of them live below the poverty line. Aim:The purpose of this article is to describe and to analyze the roles of NGOs in alleviating poverty in aborigines habitat in Malaysia and India. Methodology: A descriptive study comprising of results of the need based outreach projects taken up by NGOs in these two countries. Research is based on studies done on the important contributions made by NGOs in increasing the welfare of the poor people and implement various programs to empower the poor people. Results: Drawn from data gathered in two countries the authors take a close picture on their work,whereby this research article cites cases of NGO programs in improving the living conditions of the poor. Thereafter the authors have analyzed the successful performance in enhancing the quality of life of the poor. Conclusion: The NGOs activities have made positive changes for the aborigines of these countries. Their work is not philanthropical but more towards arming the aborogines with the lever to means of livelihood and lift themselves up from impoverishment.As the privileged community our support to such entrepreneurial programs is most solicited.